La rappresentazione delle conoscenze – diversi modelli delle strutture concettuali nell’ambito della linguistica cognitiva - Kosz, Aleksandra (Neophilologica, 2008)
The question of how we preserve the knowledge in our minds, especially with the evolution of cognitive studies, has become a crucial point of the cognitive analyses, and still keeps the researchers highly interested in it. We cannot be really sure what the mental structure of knowledge is, but there are some endeavours to explain it with the phenomena such as: prototype, ICM, cognitive domain, frame, script, scenario, plan, mental spaces, semantic network. This paper is an attempt to organize and compare numerous notions concerning the representation of knowledge in human mind, the notions that appear in different theories in the field of cognitive linguistics.